2018
DOI: 10.1039/c8nr05801f
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial coupling between noble metal nanoparticles and metal–organic frameworks for enhanced catalytic activity

Abstract: Metal-organic frameworks (MOFs) have great potential to become innovative heterogeneous supports for immobilizing catalytically active noble metal nanoparticles (NPs). However, unlike metal oxide supports, the interfacial interactions between noble metal NPs and MOFs are currently neglected, thus dramatically diminishing the advantage of MOFs as supports. Herein, ZIFs(Co/Zn)@M (M = Pd, Pt or Au) nanocomposites with well-defined interfaces are synthesized and used as catalysts in gas-phase CO oxidation and liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…The high-resolution N1sX PS spectrum is split into peaks at 398.4, 399.8, and 402.5 eV,attributed to pyridinic,p yrrolic,a nd graphitic Ns pecies, respectively ( Figure 3c). [35,36] The electron donation effect of the nitrogen-doped support would increase the electronic density aroundp alladium and further facilitate the formation of Pd NPs. Additionally,f our major contributions can be identified from the Pd 3d spectra of Pd/N-GNS 800 (Figure 3d Figure S3 in the Supporting Information), implying that the nitrogen-doped support can efficiently promote the reduction of Pd 2 + to Pd 0 catalytic species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution N1sX PS spectrum is split into peaks at 398.4, 399.8, and 402.5 eV,attributed to pyridinic,p yrrolic,a nd graphitic Ns pecies, respectively ( Figure 3c). [35,36] The electron donation effect of the nitrogen-doped support would increase the electronic density aroundp alladium and further facilitate the formation of Pd NPs. Additionally,f our major contributions can be identified from the Pd 3d spectra of Pd/N-GNS 800 (Figure 3d Figure S3 in the Supporting Information), implying that the nitrogen-doped support can efficiently promote the reduction of Pd 2 + to Pd 0 catalytic species.…”
Section: Resultsmentioning
confidence: 99%
“…Notably,c omparedw ith Pd/GNS 800 ,t he Pd 3d 5/2 peak of Pd/N-GNS 800 showsaclear shift to lower bindinge nergy from 335.0 to 334.7 eV.T he phenomenon indicates ac onsiderable charget ransfer from the nitrogen-doped support to Pd species, implying as trong surfacemetal interaction. [35,36] The electron donation effect of the nitrogen-doped support would increase the electronic density aroundp alladium and further facilitate the formation of Pd NPs. [37] The nitrogen-doping content in Pd/N-GNS 800 is measured to be 3.6wt% by elemental analysis( EA), and the palladium amount is evaluated to be 6.4 wt %b yi nductivelyc oupled plasma optical emission spectrometry (ICP-OES).…”
Section: Resultsmentioning
confidence: 99%
“…Some noble metal catalysts, such as Au, Pt, Pd, and Ru, can be embedded within the pores of different MOFs and COFs, which can avoid the aggregation of these catalysts and improve their catalytic activity. 149 As mentioned previously, MOF-on-MOF and MOF@COF hybrids exhibit comprehensive performances, which can combine the advantages of different frameworks. Thereby, it can be expected that these heterostructures will display extensive applications in the molecular catalysis field (Table 2).…”
Section: Applications Of Mof/cof-based Heterostructuresmentioning
confidence: 89%
“…25 We speculated that this weak electronic interaction was mainly due to the less overlap of the d orbitals between Pt NPs and Cr-O clusters in MIL-101(Cr). 23 Notably, the Pt 2+ species ratio in Pt/MIL-101(Fe) and Pt/HKUST-1 catalysts increased to 32% and 36%, respectively, revealing that Pt NPs on these two MOFs became electron deficient, compared with the bare Pt NPs. In comparison with the Cr 2p, Fe 2p, and Cu 2p XPS spectra of MIL-101(Cr), MIL-101(Fe), HKUST-1, and Pt/MOFs composites (Figures 3b-3d), the Cr 2p states remained unchanged after the deposition of Pt NPs, whereas noticeable increases in Fe 2+ species (from 61.3% to 67.7%) and Cu + species (from 22% to 41%) were observed.…”
Section: Mechanistic Studiesmentioning
confidence: 98%
“…[15][16][17][18][19][20][21] Recently, scientists found that MOFs could be used to modulate the electronic status of MNPs. [22][23][24] For instance, Zhao et al 25 demonstrated that controlling the electron transfer in Pt/MOFs improved the catalytic selectivity for hydrogenation of α,β-unsaturated aldehydes. Also, Xiao et al 26 observed that tuning the electron transfer between platinum nanoparticles (Pt NPs) and porphyrinic MOFs allowed an increase in the surface electron densities of Pt NPs and enhanced the alcohol oxidation.…”
Section: Introductionmentioning
confidence: 99%